A comparison of nutritional status of rural and urban adolescent girls from schools in North India: a cross-sectional study - Goyal, Neha (International Journal Of Community Medicine And Public Health, 2018)
Background: Adolescence is a nutritionally vulnerable period for a number of specific reasons, including high requirements for growth, eating patterns and lifestyles, risk-taking behaviour and, susceptibility to social and environmental influences. The objectives of the study were to compare the nutritional status of rural and urban school going adolescent girls by anthropometric measurements. Methods: A cross-sectional study was carried out in urban as well as rural schools of Haldwani block of district Nainital from October 2012 to September 2014. Multistage random sampling was used to select the requisite number, 770 (443 rural and 327 urban) of school going adolescent girls of 10 to 19 years of age, who were interviewed and anthropometric measurements were recorded for assessing the nutritional status. WHO 2007 growth standards for 5-19 years old for girls was followed. Height-for-age Z scores and BMI-for-age Z scores were calculated with help of WHO Anthro Plus Software version 1.0.4. Data was analysed using SPSS v.20. Results: Mean weight and mean BMI of adolescent girls in urban area was significantly higher than those in rural area, while mean height in two groups was not significantly different. Mean height-for-age and the mean BMI-for-age of the study girls was below median of the 2007 WHO reference throughout the adolescent period. Conclusions: Thinness was significantly higher in rural girls while overweight and obesity was not significantly different in rural and urban girls.